The Most Obscured AGNs in the XMM-SERVS Fields - Wei Yan; W. N. Brandt; Fan Zou; Shifu Zhu; Chien-Ting J. Chen; Ryan C. Hickox; Bin Luo; Qingling Ni; David M. Alexander; Franz E. Bauer; Cristian Vignali; Fabio Vito (The Astrophysical Journal, 2023)
We perform X-ray spectral analyses to derive the characteristics (e.g., column density, X-ray luminosity) of ≈10,200 active galactic nuclei (AGNs) in the XMM-Spitzer Extragalactic Representative Volume Survey, which was designed to investigate the growth of supermassive black holes across a wide dynamic range of cosmic environments. Using physical torus models (e.g., Borus02) and a Bayesian approach, we uncover 22 representative Compton-thick (CT; N _H > 1.5 × 10 ^24 cm ^−2 ) AGN candidates with good signal-to-noise ratios as well as a large sample of 136 heavily obscured AGNs. We also find an increasing CT fraction ( f _CT ) from low ( z < 0.75) to high ( z > 0.75) redshift. Our CT candidates tend to show hard X-ray spectral shapes and dust extinction in their spectral energy distribution fits, which may shed light on the connection between AGN obscuration and host-galaxy evolution.